2017
DOI: 10.1183/13993003.00962-2016
|View full text |Cite
|
Sign up to set email alerts
|

Standardisation and application of the single-breath determination of nitric oxide uptake in the lung

Abstract: Diffusing capacity of the lung for nitric oxide (), otherwise known as the transfer factor, was first measured in 1983. This document standardises the technique and application of single-breath This panel agrees that 1) pulmonary function systems should allow for mixing and measurement of both nitric oxide (NO) and carbon monoxide (CO) gases directly from an inspiratory reservoir just before use, with expired concentrations measured from an alveolar "collection" or continuously sampled rapid gas analysers; 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
171
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(178 citation statements)
references
References 109 publications
(220 reference statements)
5
171
2
Order By: Relevance
“…However, studies in our laboratory and others have suggested that a value greater than 1.97 should be used when converting Dm NO to Dm CO (Magini et al, 2013; Tamhane et al, 2001). For this reason, we are wary of the conclusion by the recent task force that a value of 1.97 should be utilized (Zavorsky et al, 2017). Below, we have calculated an ‘effective α’ for the finite method (see below) which can be used to directly convert DLNO to Dm CO as the α ratio does for the infinite method.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, studies in our laboratory and others have suggested that a value greater than 1.97 should be used when converting Dm NO to Dm CO (Magini et al, 2013; Tamhane et al, 2001). For this reason, we are wary of the conclusion by the recent task force that a value of 1.97 should be utilized (Zavorsky et al, 2017). Below, we have calculated an ‘effective α’ for the finite method (see below) which can be used to directly convert DLNO to Dm CO as the α ratio does for the infinite method.…”
Section: Resultsmentioning
confidence: 99%
“…While we respect the work of the recent ERS task force, we believe their findings are premature as no study has been designed to calculate an exact θ NO in vivo in humans, and we are also uncomfortable with their conclusions regarding the correct Dm NO /Dm CO (a-) ratio. Additionally, the ERS task force has not presented any new evidence for use of a finite θ NO beyond the evidence discussed above (Zavorsky et al, 2017). Therefore at this time, we suggest the continued use of the assumption that θ NO is infinite until further optimization of the finite θ NO method can be performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations